Application of Collision Detection in Arjuna's Adventure Game - Pajar Pahrudin; Siti Lailiyah; Dicky Ary Setiawan (TEPIAN, 2023)
This research makes how to build a 2 dimensional game with the theme of a young man named Arjun who is on the battlefield and is attacked by "Buto Ijo's troops and must go through attacks from Buto Ijo's troops to protect the “Banakeling” kingdom. The background in taking the theme Arjuna game with side scrolling game to make this game easy to play. In game research that was built using the stages of multimedia development and also using the collision detection method. The Arjuna’s Adventure Game is built based on Android. The design system in this study uses a flowchart. Testing is done with the White Box and Black Box.